2021
DOI: 10.3389/fmicb.2021.784025
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Gluconic Acid From Nguyenibacter sp. L1 Is Responsible for Solubilization of Aluminum Phosphate

Abstract: Phosphorus (P) deficiency is one of the major factors limiting plant growth in acid soils, where most P is fixed by toxic aluminum (Al). Phosphate-solubilizing bacteria (PSBs) are important for the solubilization of fixed P in soils. Many PSBs have been isolated from neutral and calcareous soils, where calcium phosphate is the main P form, whereas PSBs in acid soils have received relatively little attention. In this study, we isolated a PSB strain from the rhizosphere of Lespedeza bicolor, a plant well adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…A number of previous studies suggest that clay minerals may be important P-binding components in most soils and control the P adsorption capacity, which is inconsistent with this article, which may be due to the fact that there is no significant difference in the cohesive content of different tested soils (Figure 2) (Alovisi et al, 2020;Gérard, 2016;Li, Kang, et al, 2021;Li, Ni, et al, 2021;Li, Zhao, et al, 2021). Based on the results of correlation analysis, we speculate that the increase in Al d in topsoil after wildfires may be a key factor leading to the adsorption of IHP in the high-concentration stage (Table 4a) (Ahmed, Huang, et al, 2021;Ahmed, Jing, et al, 2021).…”
Section: P Adsorptioncontrasting
confidence: 85%
See 1 more Smart Citation
“…A number of previous studies suggest that clay minerals may be important P-binding components in most soils and control the P adsorption capacity, which is inconsistent with this article, which may be due to the fact that there is no significant difference in the cohesive content of different tested soils (Figure 2) (Alovisi et al, 2020;Gérard, 2016;Li, Kang, et al, 2021;Li, Ni, et al, 2021;Li, Zhao, et al, 2021). Based on the results of correlation analysis, we speculate that the increase in Al d in topsoil after wildfires may be a key factor leading to the adsorption of IHP in the high-concentration stage (Table 4a) (Ahmed, Huang, et al, 2021;Ahmed, Jing, et al, 2021).…”
Section: P Adsorptioncontrasting
confidence: 85%
“…Soil organic carbon (SOC) content was determined by the dichromate wet oxidation method; SOM content was calculated by multiplying the values of the SOC by 1.724 (Sun et al, 2018). The determination methods of different forms of Fe/Al oxides in soil were as follows: free crystalline Fe/Al oxides (Fe d , Al d ) were extracted by the disulfite‐citrate‐bicarbonate (DCB) method, while amorphous Fe oxides (Fe ox ) were extracted by the acidic ammonium oxalate method, both of which were assayed by the colorimetric method (Li, Kang, et al, 2021; Li, Ni, et al, 2021; Li, Zhao, et al, 2021). Soil texture was determined by the sieve‐pipette method, SOM was removed by oxidation with hydrogen peroxide, in which soil aggregates were dispersed.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we observed that Nguyenibacter sp. L1 isolated from the rhizosphere of the Altolerant plant Lespedeza bicolor solubilizes fixed P and alleviates the toxic effects of Al on rice by secreting organic acids (Li et al, 2021). The results of these analyses collectively suggest that the specific bacterial and fungal taxa enriched in the rhizosphere of Al-tolerant rice genotypes may potentially influence the secretion of organic acids by plants and P solubilization as well as promote plant growth, thereby modulating rice Al tolerance and P uptake efficiency.…”
Section: Liming Was the Main Factor Altering The Microbial Diversity ...mentioning
confidence: 91%
“…Although an external application of succinic acid inhibits P solubilization in legumes (e.g., chickpea) [71], several organic acids of microbial origin have been shown to participate in P solubilization in soil [70,72]. Gluconic acid is one of the P-solubilizing organic acids produced by root-associated rhizobia [63,68,73,74]. Its production by non-rhizobial bacteria including Azospirillum and Nguyenibacter is involved in the solubilization of calcium phosphate and aluminum phosphate [73,74].…”
Section: Mineral Acquisitionmentioning
confidence: 99%
“…Gluconic acid is one of the P-solubilizing organic acids produced by root-associated rhizobia [63,68,73,74]. Its production by non-rhizobial bacteria including Azospirillum and Nguyenibacter is involved in the solubilization of calcium phosphate and aluminum phosphate [73,74]. Besides gluconic acid, the solubilization of Ca and Fe phosphates could also be mediated through other organic acids [68,75].…”
Section: Mineral Acquisitionmentioning
confidence: 99%